High altitude kite mapping: evaluation of kite aerial photography (KAP) and structure from motion digital elevation models in the Peruvian Andes. Issue 15 (18th August 2018) - Wigmore, Oliver; Mark, Bryan
ABSTRACT: Researching glacier-melt impacted hydrology in the Andes motivates us to collect on-demand, high-resolution multispectral imagery, and digital elevation models (DEMs). While adverse conditions in these remote mountain locations present technical challenges for motorized unmanned aerial systems (UAS), consistent katabatic winds allow for testing lightweight Kite Aerial Photography (KAP) as an alternative. We use a KAP platform at 4000 msl in the Peruvian Andes to survey a 0.23 km 2 pro-glacial alpine meadow and wetland system. Using structure from motion we develop a 2 cm orthomosaic, dense point cloud with 101 points/m 2, and 5–100 cm DEMs. Accuracy of the DEM was found to be equivalent to a 1 m aerial lidar DEM; however, the denser point cloud derived from the KAP platform retained better definition of fine surface features. The high resolution, robustness and low acquisition cost of these platforms indicates strong potential for the monitoring of fine scale and rapid changes in mountain environments.